On Chief Architect Kasim Agha and his Waqf - Aysu Ateş (Art-Sanat)
In the architectural environment of the 17th century, where the relations between art and politics were intertwined, one of the most striking people was Architect Kasim Agha. Kasim Agha, who participated in palace intrigues rather than architecture and established relations with political figures such as the queen mother, grand vizier, and sultan’s hodja, played a role in 17th-century Ottoman political life with his efforts to bring Köprülü Mehmed Pasha to the grand vizierate. Kasim Agha, who left the chief architect in 1651 and became the kethüda (chamberlain) of Turhan Sultan, found a place in the Ottoman chronicles due to her political relations. However, he is among the important architectbuilders of the century, within the framework of the financial power he acquired, as he built a darülhadis in Istanbul and built complexes, fountains, inns, bridges, and waterways in the Balkans. The study focuses mainly on his waqf dated 1641, and in addition to the structures he built, the architect’s origin, his mansion, his family members, his architecture, and his political struggles are examined. In the study, which is based on Kasim Agha’s waqf, Ottoman archive documents, Ottoman chronicles, and kadi registers, Kasim Agha’s life was tried to be illuminated in various aspects.